Selection of treatment strategies for lumbar Brucella spondylitis: a retrospective clinical study - Liu, Changhao; Liu, Qiang; Zheng, Jianping; Niu, Ningkui; Shi, Jiandang; Yang, Zongqiang (Frontiers in Surgery, 2024)
Objective This study aims to investigate the treatment strategies for lumbar brucellar spondylitis by comparing the outcomes of pure pharmacological treatment with diseased intervertebral fixation fusion, with or without lesion clearance.Methods A total of 157 patients with lumbar brucellar spondylitis were categorized into three groups: Group A (52 cases) received pure pharmacological treatment, Group B (53 cases) underwent posterior vertebral fixation fusion, and Group C (52 cases) received posterior (or anterior) lesion clearance followed by posterior vertebral fixation fusion. Clinical data were analyzed, and the efficacy of the three treatment methods was evaluated.The surgical groups showed better outcomes at various time points compared to the pharmacological treatment group (P < 0.05). The pure fixation group outperformed the lesion clearance fusion group during the perioperative period (P < 0.05). The ESR, CRP, ODI scores, imaging evaluation and complications of the lesion clearance followed by fixation group were all better than those of the other two groups (P < 0.05). Surgical treatment groups showed no statistically significant difference in VAS scores (P > 0.05), and both were superior to the pharmacological treatment group. There were no statistically significant differences in clinical efficacy among the three groups at the last follow-up.Surgical treatment achieves early recovery goals compared to pharmacological treatment for brucellar spondylitis. However, individualized treatment principles should guide surgical decisions to select the most suitable approach for patients.